ANALISIS PANJANG CFRP KOLOM PADA PERKUATAN EXTERIOR BEAM-COLUMN JOINT BETON BERTULANG MENGGUNAKAN MIDAS FEA - Sandjaya, Arif; Fathurrahman, Muhammad Rafi; Leman, Sunarjo (JMTS: Jurnal Mitra Teknik Sipil, 2024)
With increasing knowledge and technological advances, earthquake resistance regulations are undergoing updates. Buildings that existed before the new regulations will need to be reviewed. If it turns out that the results of the review do not meet the requirements of the new regulations, then one solution is retrofitting. Fiber reinforced polymer (FRP) has emerged as a viable alternative for reinforcing reinforced concrete components. The advantages of FRP are that it is corrosion resistant, lighter than steel reinforcement, high tensile strength, and easy application. FRP can be in the form of rods, grids, or sheets. There are generally 5 types of FRP, namely glass fiber reinforced polymer (GFRP), aramid fiber reinforced polymer (AFRP), carbon fiber reinforced polymer (CFRP), basalt fiber reinforced polymer (BFRP), and natural fiber reinforced polymer (NFRP). This research will present CFRP as reinforcement for reinforced concrete beam and column connections. Variations in CFRP length in the column were analyzed using MIDAS FEA. 1 models of reinforced concrete beam and column connections were made without CFRP and 7 models with CFRP. The analysis results show that CFRP can increase the load capacity carried by the connection by up to 25% and there is a limit to the length of CFRP use due to the limited capacity of concrete. Abstrak Dengan bertambahnya pengetahuan dan kemajuan teknologi, peraturan tahan gempa mengalami pembaruan. Bangunan yang sudah ada sebelum peraturan baru perlu ditinjau kembali. Jika ternyata hasil peninjauan tidak memenuhi persyaratan dari peraturan baru, maka salah satu solusinya adalah perkuatan. Fiber reinforced polymer (FRP) telah muncul sebagai alternatif yang layak untuk perkuatan komponen beton bertulang. Kelebihan FRP adalah tahan korosi, lebih ringan dibandingkan perkuatan baja, kuat tarik yang tinggi, dan aplikasi yang mudah. FRP dapat berbentuk rod, grid, ataupun lembaran. FRP secara umum ada 5 jenis, yaitu glass fiber reinforced polymer (GFRP), aramid fiber reinforced polymer (AFRP), carbon fiber reinforced polymer (CFRP), basalt fiber reinforced polymer (BFRP), dan natural fiber reinforced polymer (NFRP). Penelitian ini akan menampilkan CFRP sebagai perkuatan pada hubungan balok dan kolom beton bertulang. Variasi panjang CFRP pada kolom dianalisis menggunakan MIDAS FEA. Dibuat 1 model sambungan balok dan kolom beton bertulang tanpa CFRP dan 7 model dengan CFRP. Hasil analisis menunjukkan CFRP dapat meningkatkan kapasitas beban yang dipikul sambungan hingga 25% dan ada batas panjang penggunaan CFRP karena terbatasnya kemampuan beton.